Influence of dental education, nutrition, and oral hygiene practices on DMFT and CPITN scores: a comparative cross-sectional study - Gökhan Karadağ; Dilek Hançerlioğulları; Merve Haberal; Akif Nalbant (BMC Oral Health)
Abstract Background This study aimed to evaluate the DMFT (Decayed, Missing, and Filled Teeth) and CPITN (Community Periodontal Index of Treatment Needs) scores, nutritional habits, and oral hygiene behaviors of first-year (Class-1) and fifth-year (Class-5) dental students at Kırıkkale University Faculty of Dentistry, and to compare these metrics with age-matched general population patients. Methods In this cross-sectional study, DMFT and CPITN scores were recorded for three distinct groups: Class 1 and Class 5 dental students, and a randomly selected group of age-matched patients from the general population who applied to our clinic. The effects of individual social and behavioural characteristics on these indexes were examined. Kruskal-Wallis H test was used for comparisons between groups. Chi-Square analysis was used in the evaluation of categorical data. A significance level of 0.05 was used. Results There was no statistically significant difference between the groups in terms for gender (p = 0.331), number of snacks (p = 0.406), tooth brushing (p = 0.069), toothbrush type (p = 0.244) and mouthwash use (p = 0.562). However, the Class-5 group showed a significant difference from the other groups with the highest number of “yes” answers in the question of visit to the dentist for a check-up (82%, p < 0.001) and the question of flossing (61%, p < 0.001). There was no statistically significant difference in overall DMFT (p = 0.053) or CPITN (p = 0.329) scores between the groups. However, when the subcomponents of the DMFT index were evaluated separately, the Class-5 group had the statistically significantly lowest mean decayed teeth (D) compared to the other two groups (p < 0.001), and the statistically significantly highest mean filled teeth (F) score compared to the other two groups (p < 0.001). Conclusion Oral health behaviors and outcomes are influenced by dental education level.